Pengaruh Pemberian Dosis Pupuk Bokasi terhadap Pertumbuhan dan Hasil Tanaman Mentimun - Fandi Ahmad (BIOEDUSAINS: Jurnal Pendidikan Biologi dan Sains, 2020)
This research aims to find out the effect of dosing bokasi fertilizer on the growth and yield of cucumber crops. The study was conducted from June to September 2019. This study used Randomized Group Design (RAK) consisting of 4 treatment levels namely B0 = No treatment, B1 = Bokashi 3 tons. Ha-1 (6 kg/ bedeng), B2 = Bokashi 5 tons. Ha-1 (10 kg/bedeng), B3 = Bokashi 7.5 tons. Ha-1 (15 kg/ bedeng), B4 = Bokashi 10 tons. Ha-1 ( 20 kg / bedeng). Each treatment was repeated three times, resulting in 15 studies. What if the results of the analysis show a noticeable difference then it will be followed by a real honest difference test (BNJ) of 0.5%. The results showed that the administration of bokashi fertilizer with a dose of 5 Ton.Ha-1 in cucumber plants can give good results to plant growth, starting from the length of the plant is 16.13cm, the number of leaves at the age of 2 MST is 11.83 and at the lifespan of 4 MST is 25.67 strands, the flowering life is 27.67 days, and the weight of the fruit is 2.37 kg. While the dose of bokashi fertilizer 7,5 Ton.Ha-1 on cucumber plants can be seen in the number of fruits that is 6,00 pieces / plant. In conclusion, the use of bokashi fertilizer 5 Ton.Ha-1 has a good influence on the growth of cucumber plants, as well as the use of bokashi fertilizer 7.5 Ton.Ha-1 provides good results for cucumber plants. Keywords: Dosage, Bokashi Fertilizer, Cucumber, Plant Growth